In vitro and in vivo studies on CCR10 regulation by Annexin A1 - Rodrigues-Lisoni, F. C.; Mehemet, D. K.; Peitl, P.; John, C. D.; Tajara, E.; Buckingham, J. C.; Solito, E. (Elsevier B.V., 2006)
The mode of action of annexin A1 (ANXA1) is poorly understood. By using rapid subtraction hybridization we studied the effects of human recombinant ANXA1 and the N-terminal ANXA1 peptide on gene expression in a human larynx cell line. Three genes showed strong downregulation after treatment with ANXA1. In contrast, expression of CCR10, a seven transmembrane G-protein coupled receptor for chemokine CCL27 involved in mucosal immunity, was increased. Moreover the reduction in CCR10 expression induced by ANXA1 gene deletion was rescued by intravenous treatment with low doses of ANXA1. These findings provide new evidence that ANXA1 modulates gene expression. (c) 2006 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
Keywords: gene expression; host defence; annexin A1-null mice; epithelial cells; annexin A1